Ageing and youth cultures
1 online resource (208 pages)
Keywords: What happens to punks, clubbers, goths, riot grrls, soulies, break-dancers and queer scene participants as they become older? For decades, research on spectacular 'youth cultures' has understood such groups as adolescent phenomena and assumed that involvement ceases with the onset of adulthood. In an age of increasingly complex life trajectories, Ageing and Youth Cultures is the first anthology to challenge such thinking by examining the lives of those who continue to participate into adulthood and middle-age. Showcasing a range of original research case studies from across the globe, the chapters explore how participants reconcile their continuing involvement with ageing bodies, older identities and adult responsibilities. Breaking new ground and establishing a new field of study, the book will be essential reading for students and scholars researching or studying questions of youth, fashion, popular music and identity across a wide range of disciplines.